Smart fog radio access networks for 6G:architecture and key technologies - Xian ZHANG; Xueyan CAO; Binghong LIU; Yuan AI; Chenxi LIU (Dianxin kexue)
Taking full advantage of fog radio access network (F-RAN),non-orthogonal multiple access techniques,and artificial intelligence techniques,smart fog radio access networks (S-FRAN) have been envisioned as a promising framework to fulfill the stringent requirements of 6G wireless network,such as ultra-high data rate,ultra-low latency,and ultra-large number of devices.The principles of S-RAN were firstly presented.Based on which,the key technol-ogies,research progress and standardization of S-FRAN were introduced.Finally,the challenges of S-FRAN were identified.